WRITING A CHILDREN STORY BOOK: ROSALINE THE BEAUTIFUL ROSE - Josephine Lunardi; Stefanny Irawan (Institute of Research and Community Outreach - Petra Christian University, 2016)
This project brings up an issue about beauty concept in a form of children’s story book with fantasy genre for children at the ages of 12 to 15. The story shows some beauty concepts in the world through the main character’s fantastical adventure. The main character of this story is a beautiful little girl who always wants to be the most beautiful girl wherever she is. The main character thinks that beauty will help her to gain attention from everybody, and she loves to be the center of attention. The beauty concept obsesses her very much because of the beauty hegemony that appears in her society. Then through the magical journey in the four countries, the main character learns that beauty is not something as simple as the way she knows about it before. The main character experiences the false consciousness of beauty concepts from the society conditioning. In the end of the story, the main character then realizes that inner beauty is far more important than physical beauty.